The Interaction of Human Pathogenic Fungi With C-Type Lectin Receptors - Goyal, Surabhi; Castrillón-Betancur, Juan Camilo; Klaile, Esther; Slevogt, Hortense (Frontiers in Immunology, 2018)
Fungi, usually present as commensals, are a major cause of opportunistic infections in immunocompromised patients. Such infections, if not diagnosed or treated properly, can prove fatal. However, in most cases healthy individuals are able to avert the fungal attacks by mounting proper anti-fungal immune responses. Among the pattern recognition receptors (PRRs), C-type lectin receptors (CLRs) are the major players in antifungal immunity. CLRs can recognize carbohydrate ligands such as β-glucans and mannans, which are mainly found on fungal cell surfaces. They induce pro-inflammatory immune reactions including phagocytosis, oxidative burst, cytokine and chemokine production from innate effector cells as well as activation of adaptive immunity via Th17 responses. CLRs such as Dectin-1, Dectin-2, Mincle, Mannose receptor (MR) and DC-SIGN can recognize many disease-causing fungi and also collaborate with each other as well as other PRRs in mounting a fungi-specific immune response. Mutations in these receptors affect the host response and have been linked to a higher risk in contracting fungal infections. This review focuses on how CLRs on various immune cells orchestrate the antifungal response and on the contribution of single nucleotide polymorphisms (SNPs) in these receptors towards the risk of developing such infections.